2021
DOI: 10.3390/genes13010082
|View full text |Cite
|
Sign up to set email alerts
|

Effect of miR-302b MicroRNA Inhibition on Chicken Primordial Germ Cell Proliferation and Apoptosis Rate

Abstract: The primordial germ cells (PGCs) are the precursors for both the oocytes and spermatogonia. Recently, a novel culture system was established for chicken PGCs, isolated from embryonic blood. The possibility of PGC long-term cultivation issues a new advance in germ cell preservation, biotechnology, and cell biology. We investigated the consequence of gga-miR-302b-5P (5P), gga-miR-302b-3P (3P) and dual inhibition (5P/3P) in two male and two female chicken PGC lines. In treated and control cell cultures, the cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 47 publications
(59 reference statements)
0
5
0
Order By: Relevance
“…This miRNA expression pattern differs from those of other miRNAs; for instance, miR-302 is upregulated in E5.5–6.5 epiblasts but is almost absent in mouse PGCs upon their specification ( Parchem et al, 2014 ; Paikari et al, 2017 ). This is in contrast with the miR-302 family in chicken, involved in regulating PGC proliferation ( Rengaraj et al, 2013 ; Lázár et al, 2021 ). gga-miR-17-302b and miR-17-5p affect PGC proliferation by regulating glucose phosphate isomerase ( GPI ) expression ( Rengaraj et al, 2013 ).…”
Section: Non-coding Rnamentioning
confidence: 69%
See 1 more Smart Citation
“…This miRNA expression pattern differs from those of other miRNAs; for instance, miR-302 is upregulated in E5.5–6.5 epiblasts but is almost absent in mouse PGCs upon their specification ( Parchem et al, 2014 ; Paikari et al, 2017 ). This is in contrast with the miR-302 family in chicken, involved in regulating PGC proliferation ( Rengaraj et al, 2013 ; Lázár et al, 2021 ). gga-miR-17-302b and miR-17-5p affect PGC proliferation by regulating glucose phosphate isomerase ( GPI ) expression ( Rengaraj et al, 2013 ).…”
Section: Non-coding Rnamentioning
confidence: 69%
“…gga-miR-17-302b and miR-17-5p affect PGC proliferation by regulating glucose phosphate isomerase ( GPI ) expression ( Rengaraj et al, 2013 ). Another study showed that the inhibition of gga-miR-302b-5p (5p) and/or gga-miR-302b-3p (3p) differentially influences PGCs proliferation and the rate of apoptosis, implying the complex influence of the miR-302b family on PGCs proliferation ( Lázár et al, 2021 ).…”
Section: Non-coding Rnamentioning
confidence: 99%
“…When GPI is knocked down, oxygen consumption is restored and glycolytic activity is reduced. Downregulation of GPI expression can reduce cell migration and sensitize tumor cells to drugs (Lázár et al, 2021; Shao et al, 2020). In acute hepatitis, acute myocardial infarction, malignant tumor and other diseases, the serum GPI activity is significantly increased, and it is positively correlated with the severity of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…They demonstrated that miR-181a* downregulates the expression of nuclear receptor subfamily 6 group A member 1 ( NR6A1 ), and homeobox A1 ( HOXA1 ), suggesting that miR-181a* regulates inappropriate meiosis and somatic differentiation of chicken PGCs in different pathways [ 110 ]. Other studies have also identified and characterized miRNAs involved in maintaining the integrity of chicken PGCs, such as the regulation of DNA methylation [ 54 ], glucose metabolism [ 111 ], and apoptosis [ 112 ]. In contrast, lncRNAs are non-coding RNAs composed of over 200 nucleotides and possess various functions, such as epigenetic, transcriptional, and translational regulation, via lncRNA–RNA or lncRNA–protein interactions [ 113 ].…”
Section: Integrity Of Chicken Pgcsmentioning
confidence: 99%